Fiscal Policy and Economic Development - Mourmouras, Alex (IMF Working Papers; Working Paper, 2008)
This paper offers possible explanations for three generally observed facts about fiscal policy and development: (F1) The relative size of government increases as an economy develops, (F2) The rise in government and taxation are associated with rising or constant economic growth rates, and (F3) Today's developing countries have larger government sectors than did today's developed countries at similar stages of development. The explanations for these facts are based on the structural transformation from traditional (mostly agricultural) to modern (industrial and post-industrial) production, rising public infrastructure investment, and less representative governments in many of today's developing economies.